The Middle East. Political and social development. By R. Stephens. The problem of Egypt. By T.E.M. Mckitterick. Russia and the Middle East. By G. Wheeler, etc ([London], 1957)
Special number of "The political quarterly", vol. 28, 2 (April-June 1957).